In silico & In vitro study to estimate Plasma Protein Binding of anti-parasitic compounds for Sleeping sickness (Human African trypanosomiasis) - James, Akash (My University, 2022)
Human African trypanosomiasis (HAT), also known as sleeping sickness, is a disease caused by a group of parasites called Trypanosoma brucei (Tb). The two main types causing HAT are T. brucei gambiense and T. brucei rhodesiense. T. brucei gambiense is the most common form of HAT, accounting for ninety seven percent of all reported cases of sleeping sickness. According to WHO, HAT is endemic in 36 sub-Saharan African countries. The disease can lead to death during the second stage if left untreated. Several drugs have been developed for the first stage such as pentamidine and suramin, and for the second stage such as melarsoprol, nifurtimox-eflornithine combination therapy (NECT). In 2019, fexinidazole was introduced as an oral treatment for the first stage and non-severe second stage of HAT. Several antiparasitic compounds prepared by our collaborator’s research group at the University of Graz, Austria showed varying levels of activity against Tb in vitro, whereas the compounds had only a moderate in vivo effect if at all. The suggested reason for the poor in vivo activities is that the compounds may bind tightly to plasma proteins, or they are metabolized before reaching the target sites for therapeutic effect. The prediction of plasma protein binding is of paramount importance in the pharmacokinetics characterization of drugs, as it causes significant changes in volume of distribution, clearance and drug half-life. Human serum albumin (HSA), an abundant plasma protein, can bind a remarkable variety of drugs impacting their delivery and efficacy and ultimately altering the drug’s pharmacokinetic and pharmacodynamic properties. In this current investigation, the overall aim was to investigate whether a strong HSA binding could be a probable reason for the poor in vivo activity of the provided antiparasitic compounds. The interaction of the antiparasitic compounds with HSA was studied computationally by docking them in the HSA drug binding site I and II. The compounds with the highest docking score were additionally studied using molecular dynamics simulations to evaluate the stability of the binding interactions. Moreover, the HSA binding affinity of the compounds was estimated by calculating the binding free energies using the MM-GBSA approach. In addition, experimental HSA binding studies using Microscale thermophoresis (MST) were conducted for some of the compounds. The results of the in silico studies suggest that majority of the investigated compounds may bind to HSA with varying affinity whereas a few of them did not show favorable binding interactions with HSA. Further, none of the compounds studied in vitro by MST showed HSA binding. In sum, plasma protein binding may be the reason for the in vivo inactivity for some of the investigated antiparasitic compounds.
Keywords: Sleeping Sickness, Human Serum Albumin, Molecular Dynamics Simulation, binding free energy estimation, Microscale thermophoresis